Biomass Production Trials on Sodic Site - Chaturvedi, A. N.; Behl, H. M. (Indian Forester, 1996)
Usar soils occupy about 7 million hectare of land in India. These lands have reached a stage of very low productivity due to overuse. Twelve tree species were planted during October 1981 at uniform spacing of 1.5 × 1.5 m in plots of 40 m × 40 m. The plots were analyzed for their biomass production from two to eight years. The analysis was based on destructive sampling of trees from the surround and forming regression equations. The form of the equation was Weight = a + b D2H. Biomass estimations were carried out in the inner plots of 20 m × 20 m leaving a surround of 10 m all-round. The growing stock shows changing pattern. The species that grew fast in early phase did not perform well in later years. The site amelioration was studied at the beginning of thc trial and after four years. The site has shown all-round improvement though the rates vary with the species. No biomass was removed from the site and leaves, branches, pods etc. falling on the ground was permitted to recycle nutrients.